2021
DOI: 10.18517/ijaseit.11.1.9432
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variability in Soil Water Content Profiles under Young and Mature Oil Palm Plantations in North Bengkulu Regency

Abstract: Soil water content (SWC) profile refers to the vertical distribution of volumetric SWC at a certain depth of soil concerning the plant water availability. The current study aimed to evaluate the vertically spatial distributions and temporal variations in SWC profiles under young and mature oil palm trees during the end period of the rainy season. Twenty couples of sensors were inserted into 5 cm soil depth intervals up to 100 cm. Each sensor pair was connected to the dielectric instrument to measure the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
0
0
1
Order By: Relevance
“…There were significant differences in final humidity among treatments (p ≤ 0.05) in the three depths, being higher in the area with 5-yearold oil palm due to a higher q inicial inf compared to the other treatments (Tables 1, 2, and 3). Humidity q inicial inf and q final inf in the 25-year-old plantation were higher than the 11-year-old plantation in the three depths; this is consistent with values reported by Hermawan et al (2021), who found soil humidity is higher in mature plantations than in young plantations. In addition, the incorporation of leaf litter into the soil implies greater storage capacity for water, air, root growth, and macro-and microorganism populations (Arias, 2021).…”
Section: Field Capacity (Cc) and Permanent Wilting Point (Pmp)supporting
confidence: 91%
“…There were significant differences in final humidity among treatments (p ≤ 0.05) in the three depths, being higher in the area with 5-yearold oil palm due to a higher q inicial inf compared to the other treatments (Tables 1, 2, and 3). Humidity q inicial inf and q final inf in the 25-year-old plantation were higher than the 11-year-old plantation in the three depths; this is consistent with values reported by Hermawan et al (2021), who found soil humidity is higher in mature plantations than in young plantations. In addition, the incorporation of leaf litter into the soil implies greater storage capacity for water, air, root growth, and macro-and microorganism populations (Arias, 2021).…”
Section: Field Capacity (Cc) and Permanent Wilting Point (Pmp)supporting
confidence: 91%
“…Hal tersebut mencerminkan bahwa ruang pori total pada lapisan atas lebih besar akibat bahan organik yang lebih tinggi, sehingga dapat diisi oleh air lebih besar pula. Penelitian Hermawan et al (2021) menunjukkan bahwa distribusi vertikal kepadatan isi tanah dapat menjadi penyebab variabilitas spatiotemporal dalam profil kadar air. Lapisan yang lebih longgar di seluruh profil tanah mungkin menyebabkan proporsi pori-pori drainase yang lebih besar dan menghasilkan kandungan air yang lebih sedikit dibandingkan dengan lapisan yang lebih padat.…”
Section: Berat Volume Tanah Berat Jenis Tanah Dan Porositasunclassified